Co-Microencapsulation of Flavonoids from Yellow Onion Skins and Lactic Acid Bacteria Lead to Multifunctional Ingredient for Nutraceutical and Pharmaceutics Applications - Ștefania Adelina Milea; Mihaela Aida Vasile; Oana Crăciunescu; Ana-Maria Prelipcean; Gabriela Elena Bahrim; Gabriela Râpeanu; Anca Oancea; Nicoleta Stănciuc (Pharmaceutics, 2020)
In this study, flavonoids extracted from yellow onion skins and Lactobacillus casei were encapsulated in a combination of whey protein isolate, inulin and maltodextrin with an encapsulation efficiency of 84.82 ± 0.72% for flavonoids and 72.49 ± 0.11% for lactic acid bacteria. The obtained powder showed a flavonoid content of 89.49 ± 4.12 mg quercetin equivalents/g dry weight (DW) and an antioxidant activity of 39.27 ± 0.45 mM Trolox/g DW. The powder presented a significant antidiabetic and anti-inflammatory potential, with an inhibitory effect on α-amylase, lipase and lipoxygenase of 76.40 ± 2.30%, 82.58 ± 3.36% and 49.01 ± 0.62%, respectively. The results obtained for in vitro digestion showed that the coating materials have a protective effect on the flavonoids release. Cytotoxicity results indicated that the powder was cytocompatible up to a concentration of 500 μg/mL. The functional potential of the powder was tested by adding in a selected food matrix, highlighting a good stability of the phytochemicals, whereas an increase with 1 log cell forming unit (CFU)/g DW was observed after 21 days of storage. The obtained results are promising in the valorization of natural antioxidants in combination with lactic acid bacteria in order to develop multifunctional ingredients with value-added for food and pharmaceutics applications.